Antibacterial Activity of Moringa (Moringa oleifera L.) Leaf Extract Against Salmonella typhi: A Study for Monograph Development in Biology Education - Efriyandika, Toni; Putra, Resna Hegi; Pantiwati, Yuni (ISEJ : Indonesian Science Education Journal, 2025)
Salmonella typhi, the causative agent of typhoid fever, has increasingly developed resistance to conventional antibiotics, necessitating research into alternative antimicrobial agents. Moringa oleifera L. is a medicinal plant rich in phytochemical compounds including flavonoids, saponins, tannins, and terpenoids with documented antibacterial properties. This study examined the antibacterial activity of ethanol extract of moringa leaves against S. typhi growth, and evaluated the validity and practicality of a monograph developed from these experimental findings for undergraduate microbiology education. Using a True Experimental Research design with a Completely Randomized Design (CRD), the antibacterial activity was assessed through the Kirby-Bauer disc diffusion method at concentrations of 12.5%, 25%, 50%, and 100%, with Aztreonam as positive control. The monograph development followed the 4-D model (Define, Design, Develop, Disseminate). Results demonstrated that all extract concentrations significantly inhibited S. typhi growth (p = 0.000), with the highest inhibition zone diameter of 14.18 mm at 100% concentration, classified as strong inhibition. Higher concentrations consistently produced larger inhibition zones, indicating a dose-dependent antibacterial effect. The developed monograph achieved validity scores of 91.67% (content expert) and 92.85% (media expert), both categorized as valid. Practicality testing with 14 students yielded a score of 87.93%, indicating the monograph is highly practical for use in microbiology courses. These findings confirm moringa leaf extract as a promising natural antibacterial agent and establish its viability as research-based educational material.